Deciphering the role of Paenibacillus strain Q8 in the organic matter recycling in the acid mine drainage of Carnoulès - Delavat François; Phalip Vincent; Forster Anne; Lett Marie-Claire; Lièvremont Didier (Microbial Cell Factories, 2012)
Abstract Background The recycling of the organic matter is a crucial function in any environment, especially in oligotrophic environments such as Acid Mine Drainages (AMDs). Polymer-degrading bacteria might play an important role in such ecosystem, at least by releasing by-products useful for the rest of the community. In this study, physiological, molecular and biochemical experiments were performed to decipher the role of a Paenibacillus strain isolated from the sediment of Carnoulès AMD. Results Even though Paenibacillus sp. strain Q8 was isolated from an oligotrophic AMD showing an acidic pH, it developed under both acidic and alkaline conditions and showed a heterotrophic metabolism based on the utilization of a broad range of organic compounds. It resisted to numerous metallic stresses, particularly high arsenite (As(III)) concentrations (> 1,800 mg/L). Q8 was also able to efficiently degrade polymers such as cellulose, xylan and starch. Function-based screening of a Q8 DNA-library allowed the detection of 15 clones with starch-degrading activity and 3 clones with xylan-degrading activity. One clone positive for starch degradation carried a single gene encoding a "protein of unknown function". Amylolytic and xylanolytic activities were measured both in growing cells and with acellular extracts of Q8. The results showed the ability of Q8 to degrade both polymers under a broad pH range and high As(III) and As(V) concentrations. Activity measurements allowed to point out the constitutive expression of the amylase genes and the mainly inducible expression of the xylanase genes. PACE demonstrated the endo-acting activity of the amylases and the exo-acting activity of the xylanases. Conclusions AMDs have been studied for years especially with regard to interactions between bacteria and the inorganic compartment hosting them. To date, no study reported the role of microorganisms in the recycling of the organic matter. The present work suggests that the strain Q8 might play an important role in the community by recycling the scarce organic matter (cellulose, hemicellulose, starch...), especially when the conditions change. Furthermore, function-based screening of a Q8 DNA library allowed to assign an amylolytic function to a gene previously unknown. AMDs could be considered as a reservoir of genes with potential biotechnological properties.